Micro level realities and policy coherence for enhancing climate change resilience in Asia - Singh, Naveen P.; Byjesh, K.; Bantilan, MCS (2012)
The climate change has been recognized by the world community as a potential threat to environment, ecosystem, and development. The impacts are not spatially similar and Asia s rural poor are more challenged of its consequences. ICRISAT with support of ADB have tracked the climatic trends, identified vulnerable regions to climate change and ascertained the farmer s perception through quantitative and qualitative means for deciphering the adaptation strategies and constraints to adaptation in South Asia (Bangladesh, India, Sri Lanka), South East Asia (Thailand, Vietnam) and China. A comprehensive approach (Q2) was designed to imbibe the information at different levels of its significance. Climatic analysis to understand the trends in climate and climate change vulnerability assessment of the regions and sub-regions was carried and later 22 villages were selected from these vulnerable regions for understanding ground level realities of climate change impacts and adaptation strategies.